Oralidade e argumentação : análise de uma proposta de ensino por meio do gênero debate - Belarmino, Annabell Santos (2018)
School tradition usually determines the genres that are studied throughout the student life, ignoring the most common genres of the quotidian and just focusing the school ones, that generally belong to the written modality. For a long time, school has contemplated too much the genres referring to the narrative discourse and the literary discourse, being unrelated to other genres of daily life. This work aims to investigate aspects of argumentative activity, based on orality practice in the school context. It also proposes the elaboration of a didactic model that involves literacy events concerning the comprehension and systematization of oral argumentation. Therefore, we used the design of Dolz and Schneuwly (2004) called Didactic Sequence (DS), which is an organization of pedagogical activities with a view to the domain of a given textual genre and that provides learning in the use of the language in diferent communicative situations, to elaborate the activities applied in the classroom. For this, we developed an action research in a class of 9th grade (Basic education - 9 years). The choice of the public of this research was due to the necessity of extension of the argumentative competence, mainly because this competence is contemplated in the PCN (1998 ), but little clarified and used in elementary school. Based on these considerations, we believe that the contribution of oral expression in the context of the classroom is very relevant, through an oral genre - regulated debate, in order to support the construction of the argument within the school space, in a close context the reality. Finally, orality and argumentation are everyday activities in school spaces, but they are seldom used as teaching objects and there is little research that vehemently addresses these two language activities together.